1999
DOI: 10.2527/1999.77123289x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine fed during gestation and lactation on sow and litter performance.

Abstract: Multiparous sows (n = 307) were used to evaluate the effects of added dietary L-carnitine, 100 mg/d during gestation and 50 ppm during lactation, on sow and litter performance. Treatments were arranged as a 2 (gestation or lactation) x2 (with or without L-carnitine) factorial. Control sows were fed 1.81 kg/d of a gestation diet containing .65% total lysine. Treated sows were fed 1.59 kg/d of the control diet with a .23 kg/d topdressing of the control diet that provided 100 mg/d of added L-carnitine. Lactation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
90
6
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 15 publications
17
90
6
6
Order By: Relevance
“…Supplementation of L-carnitine in sows during gestation results in higher sow weights and higher piglet and litter weights at parturition and (therefore) at weaning [17]. It is not clear from this sow trial whether other milk production parameters than milk composition, for example duration or quantity, were affected by L-carnitine supplementation.…”
mentioning
confidence: 86%
“…Supplementation of L-carnitine in sows during gestation results in higher sow weights and higher piglet and litter weights at parturition and (therefore) at weaning [17]. It is not clear from this sow trial whether other milk production parameters than milk composition, for example duration or quantity, were affected by L-carnitine supplementation.…”
mentioning
confidence: 86%
“…The mechanism of action might be based on endocrinological changes. It was recently observed in sows that carnitine supplementation during pregnancy raises concentrations of insulin and IGF-1 in the blood [11]. McCarthy [12] postulates that adding carnitine to a lowfat diet can enhance the weight loss effect.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that supplementing sow diets with L-carnitine during pregnancy and lactation elevated litter size and increased the weight of piglets at birth and weaning (Musser et al, 1999;Eder et al, 2001;Ramanau et al, 2002). L-carnitine has been shown to affect several key enzymes involved in protein and lipid metabolism in pigs; therefore, it has been hypothesized that L-carnitine may modify some indices of blood lipid metabolism (Woodworth et al, 2004).…”
Section: Introductionmentioning
confidence: 99%